Impeachment of the King: A Constitutional Thought of Raja Ali Haji - Rilo Pambudi. S (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2025)
This article aims to reveal Raja Ali Haji's views on the impeachment of the head of state (the King) in a monarchical system. This idea indicates that he supported an accountable and non-absolute government. The analysis is conducted through socio-legal studies to offer a different perspective on Raja Ali Haji and his thoughts. Historical contexts and interpretations of Raja Ali Haji's literary works are used in this article to explore these ideas. The findings show that the concept of impeaching the King must be based on valid reasons and proper considerations. Even then, this impeachment should not be carried out immediately; it must go through a special institution, Ahl al-Hall wa al-Aqd. His caution in discussing the issue of impeachment demonstrates that it should not be the first solution but a last resort if other methods can no longer resolve the issues. Therefore, he emphasized the importance of moral responsibility in governing the state and administration.